Psychotic Disorder due to Withdrawal of Barbexaclone - Kuloglu, Murat; Korkmaz, Sevda; Saglam, Sadullah; Atmaca, Murad (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2013)
[Abstract Not Available]
Barbeksaklon yoksunlu?una ba?lı psikotik bozukluk
Keywords: Propylhexedrine Benzedrex; Abuse; Risk